The Modulating Role of Stress in the Onset and Course of Tourette's Syndrome: A Review. (March 2014) - Buse, Judith; Kirschbaum, Clemens; Leckman, James F.; Münchau, Alexander; Roessner, Veit
Accumulating data indicate a common occurrence of tic exacerbations and periods of psychosocial stress. Patients with Tourette's syndrome (TS) also exhibit aberrant markers of hypothalamic-pituitary-adrenal (HPA) axis activation. Based on these findings, a functional relationship between stress and tic disorders has been suggested, but the underlying mechanism of how stress may affect tic pathology remains to be elucidated. We suggest that dopaminergic and noradrenergic neurotransmission as well as immunology play a crucial role in mediating this relationship. Two possibilities of causal direction might be assumed: (a) psychosocial stress might lead to an exacerbation of tics via activation of HPA axis and subsequent changes in neurotransmission or immunology and (b) TS-related abnormalities in neurotransmission or immunology result in a higher vulnerability of affected patients to respond to psychosocial stress with a strong activation of the HPA axis. It may also be the case that both assumptions hold true and interact with each other.